2010
DOI: 10.1007/s00464-010-1096-9
|View full text |Cite
|
Sign up to set email alerts
|

Force measurement platform for training and assessment of laparoscopic skills

Abstract: BackgroundTo improve endoscopic surgical skills, an increasing number of surgical residents practice on box or virtual-reality (VR) trainers. Current training is mainly focused on hand–eye coordination. Training methods that focus on applying the right amount of force are not yet available.MethodsThe aim of this project is to develop a system to measure forces and torques during laparoscopic training tasks as well as the development of force parameters that assess tissue manipulation tasks. The force and torqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 8 publications
(7 reference statements)
4
54
1
Order By: Relevance
“…These results are in agreement with previous studies of force exertion in suturing and knot-tying in laparoscopic surgery [2,4]. This showed that even though all participants were made aware that knot-tying force was measured, novices still have a tendency to be rougher when cinching knots during vessel ligations.…”
Section: Performance Metricssupporting
confidence: 94%
“…These results are in agreement with previous studies of force exertion in suturing and knot-tying in laparoscopic surgery [2,4]. This showed that even though all participants were made aware that knot-tying force was measured, novices still have a tendency to be rougher when cinching knots during vessel ligations.…”
Section: Performance Metricssupporting
confidence: 94%
“…Force-related metrics have been mostly validated for suturing tasks [49,50,56]. Additionally, Rosen et al demónstrate that experienced surgeons apply higher [56].…”
Section: Clinical Definition Of Metricsmentioning
confidence: 99%
“…Sensing was performed by a specially built system, the BlueDragon, a bulky device with built-in mechanical sensors. More recently, Horeman et al have approached tool/tissue forces detection by means of a pressure platform placed under the box trainer task (Horeman et al, 2010). However, movement sensing has been one of the most common approaches followed.…”
Section: Alternative Technologies For Objective Surgical Evaluationmentioning
confidence: 99%
“…The first ones include all those related with movements of hands and tools performed during a task: total path length, economy of movements, speed, motion smoothness, etc. Force related metrics, such as tool-tissue interactions, have also been studied by Rosen et al (Rosen et al, 2002), and, more recently, by Horeman et al (Horeman et al, 2010). Quality metrics, on the other hand, relate to the task's definition and execution.…”
mentioning
confidence: 99%